The Effect Of Changes In Corporate Income Tax Rates, Inflation And Inetrest Rates On Income Tax Revenues - Meita, Iren; Nurdiniah, Dade (Politeknik Keuangan Negara STAN, 2023)
This study aims to identify the influence analysis of the Covid-19 Many companies have experienced the impact of Covid 19 so that they have laid off their employees, which is caused by weak public consumption and activity restrictions. Therefore the government provides a policy through tax incentives, namely reducing the corporate income tax rate to 22% from 25% previously, which will also affect tax revenue. In addition, there are several influencing factors, such as inflation and BI interest rates. So the purpose of this study is to analyze the effect of corporate income tax rates, inflation, and interest rates on income tax receipts in 2012-2021. This research analysis method uses secondary data. The data obtained comes from the documentation of the Central Director General of Taxes and the official website of the Central Statistics Agency (BPS) for 3 years (2012 – 2021) every quarter. Data were analyzed using multiple regression analysis using the classical assumption test. The results of this study are that there is no significant effect between changes in rates on income tax revenues, there is a significant effect on the average profit margin between inflation on income tax revenues, and there is no significant effect between interest rates and income tax revenues.